Multifractal-cascade model for inertial and dissipation ranges based on the wavelet reconstruction method - Zhou, Long; Rauh, Cornelia; Delgado, Antonio (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2015)
The discrete wavelet is introduced to construct the turbulent velocity fields. The simple binary cascade model p model is served as the inertial range model for velocity increments. The dissipation model, which follows Foias [Phys. Fluids A 2, 464 (1990)PFADEB0899-821310.1063/1.857744] takes the form of exp(-gk). The length of inertial and dissipation ranges is computed according to the different construction levels. Based on the binary cascade theory and the proposed dissipation model, the Reynolds number regarding to the cascade process can be estimated. The dissipation rate calculated from the proposed model not only agrees with the existing experiment data, but also suggests that the dissipation rate is not an independent variable with respect to the Reynolds number.
UnivIS-Import:2018-02-22:Pub.2015.tech.ITC.stmmec.multif